(untitled) (Research, Society and Development, 2020)
Migraine is a clinical condition referred to as a common, disabling, primary, high prevalence cephalalgic disorder that produces high socioeconomic and personal impacts. She has episodic manifestations, with recurrente headache attacks, presenting with unilateral, pulsatile, moderate ou severe pain. As it is considered a very common and disabling condition, the aim of this study was to characterize, demographically and clinically, patients with migraine. This work is part of a double-blind, crossover and randomized clinical study on the application of a treatmente with photobiomodulation in migraine patientes. Forty three eligible individuals, of both genders, after na initial screening and na evaluation with neurologists, were randomized (1:1) and separated into groups A and B and completed the Migraine Disability Assessment Questionnaire (MIDAS), the 12 – Item Allodynia Symptom Checklist (ASC – 12) – Brazilian version, and the Diary of Pain (for one month). The results of the sample characterization showed a higher occurrence of migraine in women, with homogeneity in relation to age, weight, height, time of occurrence, frequency and intensity of pain between the groups. Nausea, photophobia, phonophobia and osmophobia were the most evident predisposing factors in the analyzes performed. MIDAS indicated the presence of a moderate degree of headache in both groups and ASC – 12 in group A indicated the presence of severe allodynia and in B, moderate allodynia. These data indicate that migraine causes serious problems for its patients, which interfere considerably in their quality of life.